A Humanistic-Based Peer Support Model to Promote Subjective Well-Being in Senior High School Students: Design and Development Study - Azzahrah, Humairah; Rusmana, Nandang; Saripah, Ipah; Syahril, M. Fiqri (Kuras Institute, 2025)
This study aims to design and develop a peer-based intervention model grounded in humanistic principles to enhance the subjective well-being of senior high school adolescent in Indonesia. Employing a convergent mixed-methods design, qualitative data were obtained through focus group discussions and interviews to explore students’ needs related to peer-based support, while quantitative data on subjective well-being profiles were collected from 133 students using the Subjective Well-being Inventory for High School Students (Azzahrah et al., 2024). The developed model underwent acceptability testing by four guidance and counseling teachers and was validated by four experts in the field of guidance and counseling. The model was pilot-tested on 13 students, and the results revealed a significant increase in subjective well-being scores from the pre-test (M= 80,250) to the post-test (M= 88,875), with a p-value of 0,022 (p<0,05). These findings suggest the the model demonstrates contextual relevance and a meaningful impact in supporting adolescents’ subjective well-being. This study contributes to the field of guidance and counseling by introducing a peer-based intervention model rooted in humanistic theory, which holds potential for broad and sustainable implementation within Indonesia secondary education settings.